Revision of the Agrilus vittatus species-group (Coleoptera, Buprestidae, Agrilinae) - Jendek, Eduard; Nakládal, Oto (Zootaxa, 2019)
The Agrilus vittatus species-group comprising fifteen species from the Oriental region is defined and revised. A key to species is provided and complemented with illustrations of habitus and genitalia. Five new species are described: Agrilus acacivorus sp. nov. (Myanmar); A. albizivorus sp. nov. (North India, Nepal); A. coco sp. nov. (Philippines); A. monadikos sp. nov. (Laos) and A. occultus sp. nov. (Laos, Thailand). Seven new junior subjective synonyms are proposed for following taxa: Agrilus babaulti Théry, 1930 (= bonadonai Descarpentries Villiers, 1963 syn.nov.); A. terraereginae Blackburn, 1892 (= deerratus Curletti, 2006 syn.nov.) and A. viridicupreus Saunders, 1866 (= cylindratus Kerremans, 1896 syn.nov., = albizziae Fisher, 1935 syn.nov., = javicola Fisher, 1935 syn.nov., = cariosulus Obenberger, 1935 syn.nov., = theodasae Baudon, 1968 syn.nov.).
Keywords: brouci; Animal Distribution; Philippines; Thailand; anatomické struktury zvířat; Indie; Myanmar; Thajsko; rozšíření zvířat; India; Nepal; Animals; Laos; Body Size; zvířata; Coleoptera; Filipíny; Nepál; velikost těla; Animal Structures